A Delphi-based risk analysis — Identifying and assessing future challenges for supply chain security in a multi-stakeholder environment - Markmann, Christoph; Darkow, Inga-Lena; von der Gracht, Heiko (Technological Forecasting and Social Change, 2013)
Identifying and assessing the potential impact and likelihood of future events, which might evolve into risks, are a prerequisite to identify future security challenges. In particular, risks associated with global supply chains are special since they involve a multitude of international stakeholders with different perspectives on security needs and measures. Therefore, it is essential to determine which techniques and instruments are best suited for risk assessment in complex and multi-organizational environments. The Delphi expert survey technique has proven to be a valuable instrument for long-term decision making support as well as foresight, and has a potential value for risk assessment. We contribute to this research strand and conduct a Delphi-based risk analysis. Our research concentrates on man-made risks in global supply chains which are particularly uncertain in terms of type, location, and affected supply chain partners and can therefore be classified as inherently “wicked” issues, i.e. issues that are multidimensional with often unpleasant outcomes. We illustrate that Delphi research makes a fivefold contribution to risk analysis by: (1) identifying and quantifying risks; (2) analyzing stakeholder perceptions and worldviews; (3) stimulating a global communication process; (4) identifying weak signals, outlier opinions, and wildcards; (5) and facilitating risk scenario development.
Keywords: Risk; Supply chain security; Terroristic attacks; Delphi; Multi-stakeholder; Future